Toxicological analysis of aerosols derived from three electronic nicotine delivery systems using normal human bronchial epithelial cells. (December 2020) - Pearce, K.; Gray, N.; Gaur, P.; Jeon, J.; Suarez, A.; Shannahan, J.; Pappas, R.S.; Watson-Wright, C.
Abstract: Electronic nicotine delivery systems (ENDS) are a rapidly growing global market advertised as a safer alternative to combustible cigarettes. However, comprehensive investigations of END aerosol physicochemical and toxicological properties have not been fully explored across brands to assess relative safety. In this study, we evaluated aerosols collected from three ENDS – Juul Fruit Medley (5% nicotine), Logic Power (2.4% nicotine), and Mistic (1.8% nicotine). ENDS aerosols were generated using standard machine puffing regimen and collected with a novel fluoropolymer condensation trap. Triple quadrupole-inductively coupled plasma-mass determined the presence of heavy metals in collected aerosols. The toxicological effects of ENDS aerosols on normal human bronchial epithelial cells (NHBE) were investigated using cellular viability, reactive oxygen species, oxidative stress assays, along with DNA damage assessments using the CometChip©. Results indicated the total metal concentrations within collected ENDS aerosols were higher for Mistic and Logic compared to Juul. Logic Power aerosols elicited higher reactive oxygen species levels than Mistic and Juul in NHBE after 24-h exposure. Similar dose-dependent reductions of cellular viability and total glutathione were found for each exposure. However, Logic and Juul aerosols caused greater single stranded DNA damage compared to Mistic. Our study indicates that regardless of brand, ENDS aerosols are toxic to upper airway epithelial cells and may pose a potential respiratory hazard to occasional and frequent users. Highlights: The chemical composition of electronic nicotine delivery system (END) aerosols may vary across brand. Alongside of volatile organic compounds, END aerosols may contain high levels of metals including heavy metals. High levels of lead, nickel, chromium and tin along with copper were found in popular END brands. Higher levels of DNA damage were found although metal concentrations were below the level of detection for Juul aerosols. Our data suggest infrequent or recreational use of these ENDS devices could pose unnecessary harm to respiratory cells.